WOMEN AND SOCIAL SENSIBILITIES ON THE SHORES OF CHANDRAGIRI - Dalwai, Kasturevva Basappa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Rules and regulations should make life simple, not complicated. The customs of the community are so deeply rooted that even a slight deviation from them is considered an act against the Almighty, which complicates life. From time to time, communities, religions and castes should bring about changes in the way of life and pave the way for the breath of life. The urgency of the time is to come out of the mindset of standing still and spending life in the dark. There should not be the pain of wasting life with unchangeable rules. One should also get rid of the mindset of clinging to the banyan tree planted by one’s grandfather, thinking that there is no need for changes. Sarah Abubakar’s novel ’On the Shore of Chandragiri’ vividly depicts how such a belief and custom turned a beautiful life into a cruel hell.